Required potynomial = (x -5)(x - 3 - 2i)(x - 3 + 2i) = (x - 5)(x^2 - 6x + 13) = x^3 - 6x^2 + 13x - 5x^2 + 30x - 65 = x^3 - 11x^2 + 43x - 65
Answer:
2nd, 4th and 5th one
Step-by-step explanation:
Hey There!
So remember in order for it to be a proportional relationship it has to be a straight line and it has to go through the origin (0,0)
The 2nd, 4th and 5th ones are non proportional relationships
Why? Well because they don't go through the origin
<span>A’(2, -4); B’(7, -9); C’(-2, -9)
I believe you did it correctly but over the wrong line. You were supposed to do it over line M and it looks like you did it over the X-axis.</span>
Answer:
Hello! Your answer would be below!
Step-by-step explanation:
Graph B)
Hope I helped! Ask me anything if you have questions!
L = 4 + w
l/w = 7/5
l = 7w/5
7w/5 = 5 + w
7w = 25 + 5w
2w = 25
w = 12.5
l = 4 + 12.5
l = 16.5
the dimensions are 16.5 x 12.5 cm